THE EFFECT OF THE WORK ENVIRONMENT AND TRANSFORMATIONAL LEADERSHIP ON PERFORMANCE, WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE AMONG LECTURERS - Silitonga, Mia Kartika; Toni, Nagian; Faris, Salman (JURNAL PROFIT, 2026)
This study aims to analyse the influence of transformational leadership and the work environment on lecturer performance, with organisational commitment as a mediating variable. Transformational leadership is a leadership style that emphasises value transformation, integrity, and individual empowerment within educational organisations. Meanwhile, a conducive work environment is believed to foster collaboration and support the achievement of institutional goals. The Research used a quantitative approach, distributing questionnaires to 41 lecturers as respondents, resulting in a saturated sample. The data were then analysed using Structural Equation Modelling (SEM) to examine the relationships among variables. The results indicate that transformational leadership and the work environment positively affect organisational commitment, which, in turn, improves lecturer performance. This finding underscores the important roles of leadership and the work environment in strengthening organisational commitment, enabling educational institutions to encourage continuous improvement in academic performance.